Nicaragua - Land Policy and Administration : Toward a More Secure Property Rights Regime - World Bank (Washington, DC, 2013)
This report centers on the problems stemming from land issues in Nicaragua. The report's main recommendations deal with four priority actions: institutional reform; adjustments to the legal framework; systematic regularization of land rights; and, firmly addressing previous land invasions, and preventing future invasions. The issue of land distribution, and ownership is especially critical in Nicaragua; indeed, the country underwent a revolution that aimed to redistribute land widely. As a result of policies adopted in the wake of the revolution, about 40 percent of all land in Nicaragua is now affected by conflicting claims. Such insecurity has a strong negative impact on how efficiently land is used, and how land can be transacted - which has important implications for economic growth, poverty reduction, and environmental protection. Dealing with land issues in Nicaragua is a priority - high levels of tenure insecurity, lack of clear property rights and the institutions to effectively administer them, which in turn precludes the development of land markets - and, the underutilization of productive resources - all of which contribute to adverse economic impacts, and inevitably, environmental degradation as well. The report looks at the incidence and impact of tenure insecurity in Nicaragua, at the legal and institutional issues underlying such insecurity ,and further issues policy recommendations.